IMPLEMENTATION ANALYSIS OF THE LIST OF MAJOR DRAWBACKS IN EXTERNAL QUALITY ASSURANCE IN HIGHER EDUCATION - Butenko, Andriy; Yeremenko, Olena; Trebenko, Oksana (The Modern Higher Education Review, 2025)
The article analyses the effectiveness of implementing the List of Major Drawbacks as a tool for evaluating study programmes within the external quality assurance processes and procedures in higher education. It is stated that the goals of its implementation are: unification of approaches to decision making and ensuring objectivity of evaluation in the case of similar manifestations of problems with the quality of study programmes and educational activities under them; emphasis on key aspects of compliance with legislative requirements during the design and implementation of study programmes; codification of typical problems according to the criteria for evaluating study programmes to improve the quality of the systematic analysis of the agency’s activities at the national level: strengthening the focus of the advisory and training activities of the National Agency has generally been achieved. It is emphasised that the participants in the accreditation process are fully aware of the significance of the goals set and recognise the proposed mechanism as successful and effective. Along with this, the need for improvements was identified, which did not diminish the List’s effectiveness but would enhance it. In general, the application of the List of Major Drawbacks contributed to strengthening the transparency and predictability of the accreditation procedure, ensuring a common understanding of assessment approaches among all participants in the process – higher education institutions, expert groups, sectoral expert councils and the National Agency, which, in turn, strengthened trust in the results of the assessment of study programmes in the process of external quality assurance of higher education in Ukraine.